Verification of Scale Model and Full Model for Sound Barrier Along the Highway by FEA - Nordin, Ridwan; Muhd. Hafeez (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The purpose of this research is to validate scale and full-size models for the deployment of a sound barrier along roadways. The aim is to find insertion loss that produce by scale and full size that simulate by using ANSYS Workbench Software. The study incorporates sound measurements, computational modeling, and analysis techniques to compare the sound pressure level before and after installation of barrier. The research utilizes both scale model and full-scale model. This research allows for cost effective and efficient. The trend of graph is quite different. However, the insertion loss differences for simulation and experiment is not far apart. The maximum difference is 6.01 dBA and the minimum difference is 0.08 dBA. The outcomes of this study will help to design effective and optimized sound barriers, reducing noise pollution and improving the general quality of life near roads.